Analysing mass flow rate and noise level of blowers through Ansys CFX solver. Issue 3 (2nd September 2017) - Arun kumar, P.; Senthil, P.; Naveen kumar, K.
Abstract: In general, the blowers mounted on the wind mills are designed to supply cooling effect to the power generator for the extraction of heat, but it is noticed that the axial blowers currently deployed in the windmills tend to produce insufficient cooling effect and generate high level of noise. Thus, sufficient cooling and low noise level are key parameters in the design of blowers. This study of forward-curved centrifugal blower focuses on improving the performance of an industrial blower and implementing the performance characteristics of the system derived from high-fidelity three-dimensional CFX analyses. The objective of the present study is to estimate the aerodynamic and aero acoustic parameters like mass flow rate and noise level of axial blower and centrifugal blower. The blowers are modelled and analysed using Ansys CFX solver based on industry requirements. It is observed from the analysis that centrifugal blower is more preferable to achieve sufficient cooling effect with low noise level.